Os conhecimentos relacionados ao desenvolvimento do pensamento algébrico na formação de professores dos anos iniciais : análise de produções científicas da área, documentos oficiais e sistemas de avaliação da educação no Brasil - Frasnelli, Débora Cristine (2021)
This research aimed to understand how the pedagogical knowledge necessary to teachers is constituted, regarding the development of Algebraic Thinking in students of the early years. To achieve this goal, a qualitative meta-analysis was carried out, 8 academic researches, 7 dissertations and 1 thesis that investigated the development of Algebraic Thought in the early years of Elementary Education, as well as official documents and / or fascicles of Brazilian Education documents that addressed the thematic. This analysis corpus was constituted according to previously established criteria. The meta-analysis of this corpus was developed based on the following research perspectives: identification of the elements that constitute Algebraic Thinking in official documents and in Education practiced in teaching systems; identification of the pedagogical knowledge necessary for the development of Algebraic Thought in the early years; and how the knowledge necessary for the development of Algebraic Thought in the early years is effectively present in the teaching routine. In relation to the elements that make up Algebraic Thinking, elements associated with the Generalized Arithmetic and Functional Thinking aspects were identified in all the official documents analyzed and also in an important Basic Education tool - the textbook. The specialized knowledge of the elements linked to the aspects of Generalized Arithmetic and Functional Thinking, was inferred as necessary for teachers for the development of Algebraic Thinking in the early years. However, knowledge about these elements was not effectively present in the teaching routine. In summary, the results obtained indicate that the knowledge of the content regarding Algebraic Thinking, is essentially associated with their experiences during their schooling and initial training process, which reinforces a long time to be mobilized in favor of continuing education.